Self-regulated Professional Development: A Case of Teacher-led EFL Class Observation - Ahmad, Zulfiqar; Aljohani, Othman (International Journal of Language and Literary Studies, 2024)
Lesson observations have been frequently used as a tool for teacher appraisal, teacher training, academic research, and professional development, especially in EFL contexts. However, work on self-regulated lesson observations directed purely on collaboration and reflection is not very extensive. So is the want of a study which presents the observation report of a real-time lesson. The present study adopted a teacher-led approach to conduct a peer observation of an EFL lesson on lexis. The researchers identified evaluating the lesson from two dimensions: lesson planning and lesson delivery. The findings based on the observer’s report revealed that the lesson had an overall logical shape, clear procedures, active student-teacher interactions, effective use of the instructional materials, especially the whiteboard, productive teaching strategies and techniques such as eliciting through questions and visuals, and supportive feedback. However, there was a need for improvement, especially in regard to managing the stage timings, grading the teacher’s language, and engaging the students in an interactive pattern. The study is expected to provide some useful insights to EFL researchers and practitioners interested in further research on the topic or conducting peer observations for professional growth.